Relationship Between Maximum Pull-up Repetitions and First Repetition Mean Concentric Velocity. Issue 7 (July 2018) - Beckham, George K.; Olmeda, Joshua J.; Flores, Alexandra J.; Echeverry, Julian A.; Campos, Alexus F.; Kim, Steven B.
Abstract : Abstract: Beckham, GK, Olmeda, JJ, Flores, AJ, Echeverry, JA, Campos, AF, and Kim, SB. Relationship between maximum pull-up repetitions and first repetition mean concentric velocity. J Strength Cond Res 32(7): 1831–1837, 2018—Mean concentric velocity (MCV) of exercise execution has been used by strength and conditioning professionals to improve exercise technique, provide accurate feedback, and predict exercise 1 repetition maximum. There is still limited research on velocity-based training and currently only one research study on the pull-up exercise. The primary purpose of this research was to determine whether the maximum number of pull-ups an individual can perform can be predicted by the MCV of a single pull-up repetition. Forty-nine healthy men and women were recruited who reported they could do at least 2 pull-ups. Each subject performed a standardized warm-up, then a single pull-up repetition, followed by one set of pull-up repetitions to failure. The GymAware PowerTool, a linear position transducer, was used to measure the MCV of each pull-up repetition. Both the MCV of the single repetition and first repetition of the set to failure were recorded, and the greater of the 2 was used in later analysis. Weighted least squares linear regression was used to estimate the relationship between the single-repetition MCV and maximum amount of pull-up repetitions. We observed a statistically significant linear relationship between the maximum number of pull-ups and the MCV of a single pull-up repetition (y = −6.661 + 25.556x, R 2 = 0.841). Prediction of the maximum pull-up number by a single repetition rather than testing the maximal pull-up number may improve efficiency and effectiveness of exercise testing batteries for military, police, and other populations.